Correction: Klingler, M., et al. Cholecystokinin-2 Receptor Targeting with Novel C-terminally Stabilized HYNIC-Minigastrin Analogs Radiolabeled with Technetium-99m. Pharmaceuticals 2019, 12, 13 - Maximilian Klingler; Christine Rangger; Dominik Summer; Piriya Kaeopookum; Clemens Decristoforo; Elisabeth von Guggenberg (MDPI AG, 2019)
In our paper [...]